Developing Interactive Comics As Learning Media For Civics and Indonesian Language in First Grade - Herawati, Indah Aviolita; Relmasira, Stefanus C.; Juneau, Janelle L (International Journal of Elementary Education, 2018)
This is a R&D (Research and Development) research with the goal to answer the needs of interactive comics for civics and Indonesian language learning media in 1st-grade of ‘SD Negeri Samirono 01’. Data collection techniques are used observation, experts’ judgment, pre - post tests, and evaluation sheets. Subjects on this research are first grade students at ‘SD Negeri Samirono 01’. This research used ADDIE (Analysis – Design – Develop – Implementation – Evaluation) Devleopment model. The learning media got appropriate category result with percentage 69.23% for media expert judgment and 74.28% for materials experts’ judgment. The learning activity reach into effective, by there is a difference of after using a learning media. The Post-Test average grade is 78.65, which were bigger than Pre-Test average grade is 58.27. The learning media is able to help the students reaching their optimum abilities to understand the learning materials